When You Sweep the Stairs, You Always Start from the Top - Molineus, Sebastian (World Bank, Washington, DC, 2012)
The Private Enterprise Partnership for the Middle East and North Africa (PEP-MENA) corporate governance program highlight the importance of securing a real and demonstrable commitment by a company's senior officers and directors before embarking on the journey of corporate governance reform. Indeed, two issues highlight the challenges in improving corporate governance. First, directors and officers often do not understand the meaning of corporate governance. Second, there is a lack of understanding of how corporate governance can improve the bottom line. Issues such as this can lead to resistance to change, and overcoming them is a formidable but necessary task to building the business case for companies to implement corporate governance. This smart lesson focuses on how such commitment is obtained when implementing any company-level work to effect change to a company's governance framework, policies, and practices. The note is targeted to advisory staff implementing corporate governance projects; however, it may also be applicable to other staff who engage with private sector clients.